NUMBER OF OIL AND GAS POOLS IN POORLY EXPLORED PETROLEUM PROVINCES: STATISTICAL MODELING - Livshits V.R. (My University, 2004)
The total number of oil and gas pools in a province is approximated by the Weibull distribution. The statistical performances of this number are related to the parameters of a truncated Pareto distribution. The total number of pools is estimated on the basis of size distribution of several largest pools in a province and the estimator quality is tested through Monte-Carlo imitation.